1999
DOI: 10.1115/1.3098932
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and Strength of General Helicoidal Shells

Abstract: The geometry of helical surfaces has been well studied. Several available methods of strength analysis of helicoidal shells give one a choice in solving one-dimensional or two-dimensional problems. The basic problems considered in this review article, which contains 181 references, include geometrical research, approximation and bending of helical surfaces, static analysis of helicoidal shells by analytic and numerical methods, the vibrations of pre-twisted cantilevered plates, helical tubular shells, the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This surface is formed by the translational and rotational motion of a rectilinear generatrix intersecting the axis of the surface at right angle. The parametric equations for a right helicoid can be taken as follows [16]:…”
Section: Modelling and Simulation Of Right Helicoidmentioning
confidence: 99%
“…This surface is formed by the translational and rotational motion of a rectilinear generatrix intersecting the axis of the surface at right angle. The parametric equations for a right helicoid can be taken as follows [16]:…”
Section: Modelling and Simulation Of Right Helicoidmentioning
confidence: 99%
“…However, the majority of shape structures used nowadays are limited to number of surfaces only: circular cylindrical, conical, spherical and some other traditional shapes. These surfaces are just a small part of geometrical forms available by geometry [1,[3][4][5][6][7][8][9][10][11][12].…”
Section: Main Features Of Carved Monge Surfacementioning
confidence: 99%
“…Depending on change of various parameters, for example the form of a moving line or a guiding line, the appearance of a surface will change (figs. [3][4][5]. Let us have a look on a specific case: ruled carved Monge surface ( fig.…”
Section: Geometry Of Carved Monge Surfacementioning
confidence: 99%
“…Krivoshapko [1] described some theoretical methods of static analysis of engineering structures in the form of right and oblique helicoids. Later, in a paper [2] with 181 references, the detailed analysis of the existing methods for calculating of the helicoidal thin shells was presented, as well as the issues of geometric design and profiling of the helical surfaces. The study of the existing scientific literature showed that currently the engineers know only right and oblique helicoids, although an encyclopedia [3] provides information about the five types of ruled helical surfaces (Fig.…”
Section: Introductionmentioning
confidence: 99%